Pengaruh Penerapan Model Pembelajaran Kooperatif Teknik Keliling Kelompok Terhadap Pemahaman Konsep Matematis Siswa Kelas IX SMPN 2 Lembang Jaya Kabupaten Solok Tahun Pelajaran 2012-2013 - Gufron, Muhammad; Rismen, Sefna; Anggraini, Villia (Pendidikan Matematika, 2013)
The lacking of studentsâ activities in learning mathematics and the less understanding of mathematical concept. The aims of this research are to 1) know Â how the development of student activities is by applying the model of cooperative learning of club-round technique to the grade-IX students of SMPN 2 Lembang Jaya, 2) whether the mathematical concept understanding by applying such model is better than that by using the conventional learning to the grade-IX students of SMPN 2 Lembang Jaya. Population is the students grade-IX of SMPN 2 Lembang Jaya of academic 2012/2013 years. The sampling is made randomly and the chosen samples are grade-IX 3 as an experimental class and grade-IX 4 as a control class. The type of research is an experimental research with random to subject design. The analysis technique of the data using activities observasition and test t by one side. Based on the analysis of data, it is obtained that 1) the studentsâ activities experience an improvement by applying the model of Cooperative Learning of Club-Round Technique, 2) t result 2,02 > t tabel 1,69 Â So that, the studentsâ mathematical concept understanding applying such model is better than the studentsâ mathematical concept understanding using the conventional learning to the grade-IX students of SMPN 2 Lembang Jaya of the year 2012/2013.